DEVELOPMENT OF STUDENT LEARNING MOTIVATION (International Conference on Elementary Education, 2018)
Motivation is one of the things that influence the success of student learning activities. Without motivation, the learning process will be difficult to achieve optimum success. Cultivating student learning motivation is one of the techniques in developing learning abilities and willingness. One logical way to motivate students in learning is to link learning experiences with student motivation. As a teacher and parents as much as possible should always strive to be able to increase learning motivation, especially for students who have difficulty in learning.